A multicenter, randomized, phase 3 trial comparing fixed dose versus toxicity-adjusted dose of cisplatin + etoposide in extensive small-cell lung cancer (SCLC) patients: The Small-cell-lung cancer Toxicity Adjusted Dosing (STAD-1) trial. (June 2017) - Morabito, Alessandro; Daniele, Gennaro; Costanzo, Raffaele; Favaretto, Adolfo Gino; Filipazzi, Virgilio; Rossi, Antonio; Gebbia, Vittorio; Castiglione, Federico; Cavanna, Luigi; Maiello, Evaristo; Sandomenico, Claudia; Bonanno, Laura; et al.
Highlights: We proposed toxicity adjusted dosing of cisplatin-etoposide to improve the outcome of chemonaïve SCLC patients. Adapting the dose of chemotherapy based on toxicity is feasible in most the patients. Toxicity adjusted dosing is not associated with better outcomes in SCLC. Abstract: Objectives: Data supporting the prognostic role of chemotherapy induced haematological toxicity suggest that toxicity-adjusted-dosing (TAD) of chemotherapy might improve treatment efficacy. We tested whether TAD of the cisplatin-etoposide combination might improve the response rate, in previously untreated extensive stage disease (ED)-SCLC patients, as compared with standard fixed-dosing (FD). Methods: Patients with ED-SCLC were randomized to receive either TAD or FD of cisplatin-etoposide as first-line treatment. Primary endpoint was the objective response rate (ORR) according to the RECIST 1.0 criteria, secondary endpoints included progression free survival (PFS), overall survival (OS) and toxicity. Results: Hundred-fifty-eight patients were randomized. Most patients were male, with ECOG-PS 1, without brain metastases and had not received radiotherapy before study entry. Response rate was 54.4 (95%CI: 43.5–64.9%) and 58.2 (95%CI: 47.2–68.5%) in the control and experimental arms, respectively (P = 0.75). No significant differences were found in terms of PFS (HR 1.04; 95%CI: 0.74–1.44, P = 0.84) and OS (HR1.01; 95%CI 0.71–1.42, p = 0.97). Seven patients died on treatment, one in the standard arm and 6 in the experimental arm. The most frequent cause of death was neutropenia with infection and, apart in one, death was not related to dose modification. Severe toxicity was more frequent in the experimental arm (91% vs 60%). Conclusions: In our population of chemonaïve ED SCLC patients, TAD failed to improve the ORR, PFS and OS over the FD of cisplatin-etoposide as first line chemotherapy and was associated with increased toxicity.